Clinical outcomes and predictors of a gap in direct-acting oral anticoagulant therapy in the elderly: A time-varying analysis of a nationwide cohort study - Jung, Minji; Lee, Beom Jin; Lee, Sukhyang; Shin, Jaekyu (Thrombosis Research, 2023)
Introduction: As direct-acting oral anticoagulants (DOACs) have short half-lives of around 12 h, even a short gap in DOAC therapy may diminish anticoagulation effects, increasing risks of adverse clinical outcomes. We aimed to evaluate clinical consequences of a gap in DOAC therapy with atrial fibrillation (AF) and to identify its potential predictors. Materials and methods: In this retrospective cohort study, we included DOAC users aged over 65 years with AF from the 2018 Korean nationwide claims database. We defined a gap in DOAC therapy as no claim for a DOAC one or more days after the due date of a refill prescription. We used a time-varying-analysis method. The primary outcome was a composite of death and thrombotic events including ischemic stroke/transient ischemic attack or systemic embolism. Potential predictors of a gap included sociodemographic and clinical factors. Results and conclusions: Among 11,042 DOAC users, 4857 (44.0 %) patients had at least one gap. Standard national health insurance, non-metropolitan locations of medical institutions, history of liver disease, chronic obstructive pulmonary disease, cancer, or dementia, and use of diuretics or non-oral agents were associated with increased risks of a gap. In contrast, history of hypertension, ischemic heart disease, or dyslipidemia were associated with a decreased risk of a gap. A short gap in DOAC therapy was significantly associated with a higher risk of the primary outcome compared to no gap (hazard ratio 4.04, 95 % confidence interval 2.95–5.52). The predictors could be utilized to identify at-risk patients to provide additional support to prevent a gap.
Keywords: Administration, Oral; Aged; Anticoagulants; Atrial Fibrillation; Cohort Studies; Factor Xa Inhibitors; Humans; Retrospective Studies; Stroke; Warfarin; Atrial fibrillation; Direct-acting oral anticoagulants; Elderly; Ischemic stroke; Thrombosis